Quality improvement strategies to enhance care of mechanically ventilated patients and prevent pneumonia - Berba, Regina P.
Background: Ventilator-associated pneumonia (VAP) is a frequently encountered nosocomial infection among critically-ill patients who require mechanical ventilation. It is associated with high morbidity and mortality and greatly increases hospitalization cost and length of stay. Many studies have looked into ways of preventing VAP. The greater challenge is to find the correct combination of strategies to apply these preventive methods into one's setting and decrease the occurrence of VAP. Objectives: To determine the impact of multi-faceted quality improvement (QI) strategies designed to enhance compliance to recommendations in the prevention of ventilator-associated among critically ill patients. Methodology: This study is an eight-month, three-phrase quality improvement investigation using time series analysis. It involved three adult intensive care units at a university hospital. An initial exhaustive review of literature to develop an evidence-based list of recommendations to prevent pneumonia was done through an academic conference in the university with other experts in the fields of Infectious Diseases and Pulmonary Medicine. Three key evidence-based measures know to decrease risk for ventilator-associated pneumonia were chosen and disseminated by various approaches. The three key preventive measures were: proper hand hygiene in the care of mechanically ventilated patients, proper suctioning technique and maintaining head elevation of patients at 30 - 45 degrees. In series, the following were done per ICU: education through interactive lectures with demonstration, written and verbal reminders as well as performance feedback. The interventions involved the major groups of healthcare workers in their respective ICUs and included: nurses, nurse aides, physician-in-training and medical students. Baseline measures were taken on compliance of ICU personnel to hand washing, proper suctioning techniques and putting mechanically ventilated patients on the recommended patient head elevation. The same measure were repeatedly taken by same investigators once a week over the next seven months. During the same period, all mechanically ventilated patients admitted to any of the three ICUs were followed for the development of VAP. The occurrence of VAP was initially evaluated by the physicians-in-charge of the ventilated patients and confirmed by the independent evaluation of two physicians fellows-in-training.
Outcomes Measured: The impact of multi-faceted QI interventions was determined by 1) Process outcomes that described compliance rates of health care workers to hand hygiene recommendations before and after patient care, compliance to the proper suctioning technique and compliance to maintaining patient's head and 30-45 degrees elevation; and 2) Incidence of VAP. Data Analysis: Time series analysis was used. Process outcomes such as compliance rates to each of the specific recommendations (hand hygiene, suctioning of respiratory secretions and maintaining head elevation) were described as proportions of property performed procedures over total opportunities to perform procedures. Trends of compliance rates were plotted against time. The unit of time in the x-axis of all the graphs consisted of serial two-week periods spanning the eight-month study duration and included the pre-intervention, intervention and post-intervention phases. The specific interventions were likewise incorporated in each of the plotted lines of the graphs to describe the time sequence in which they were implemented. Compliance rates to hand hygiene were analyzed according to the respective ICUs and group health care worker (i.e. nurse, physician-in-training, medical students). Compliance rates to proper suctioning and proper head position were analyzed according to the ICU. The clinical outcome of VAP was determined by the evaluation of the physician-in-charge and the two physician fellows-in-training. Differences in evaluation of the three physicians as to the clinical outcome of each of the patients were resolved by majority rule. To measure the agreement between the two fellows in training in the evaluation whether VAP occurred or not, kappa was estimated at a 95% confidence level. The VAP rate was described in two forms in each of the ICUs: 1) Monthly cumulative incidence rate (CIR) of VAP defined as the number of new cases of VAP during the study among total number of the eligible patients who were placed on mechanically ventilation that corresponding month; 2) Monthly incidence density rate (IDR) of VAP defined as the number of new cases of VAP during the study month over the total ventilator-days of the corresponding month. The incidence density rates of VAP for each month were estimated at 95% Confidence level using the Extract method of confidence interval estimation assuming a Poison distribution. Likewise, he cumulative incidence rates were estimated at 95% confidence level. For these analyses, Stata version was used.
Results: The various components of the multi-faceted interventions were introduced to each ICU in the same sequence and simultaneously across the three ICUs during the study period. A total of 320 hours was spent for repeated observations to monitor practices and hand hygiene, suctioning and head elevation. During this time 291 mechanically ventilated patients were followed for the development of VAP, of whom 37 patients were assessed to have VAP. The compliance rates of the different groups of ICU personnel were monitored and shown to increase over time with the different strategies implemented. For the practice of hand hygiene, nursing personnel were shown to improve dramatically from baseline. Hand hygiene before and after patient care was noted to reach and maintain 100% in all the three ICUs during the latter third of the study period. This positive change seen in the nurses and nurse aides was in contrast with the non-improving pattern of residents and interns. The non-improvement of performance among the residents and interns could be related to their "transient" status in the ICUs compared to the "permanent" tenure of nurses as ICU employees. For the practice of suctioning of respiratory secretions thru the endotracheal tube, which was a procedure primarily performed by nurses, compliance rates to all the steps in the proper performance of this activity likewise improved from a baseline of 0% to greater than 40% over the latter third of the study period. For the practice of putting the patient's head at 30-45 degrees elevation which was also mainly controlled by the nurses in charge of mechanically ventilated patients, 100% compliance was achieved and sustained over the latter third of the study period. Although there were differences in the evaluation of the patients by the two evaluators (fellows-in-training) as to whether they did or did not develop VAP, the kappa coefficient between the two fellows was acceptable (kappa = 0.59 [95% Confidence Interval 0.44, 0.74]). Conclusion: Within the study period when the multi-faceted quality improvement interventions were applied tot he health care providers in the three participating adult ICUs, improvement in the performance of process indicators occurred specially among the "permanent" personnel. With the improved compliance rates to hand hygiene, suctioning and head elevation, a downward trend in the incidence of VAP among mechanically ventilated patients in all the participating ICUs was also noted. The investigation is limited by time and manpower constraints. This quality improvement initiative should be pursued to sustain the positive changes that have been achieved by the interventions already introduced. Sustainability can be enhanced by including the hospital administration, clinical departments and the hospital infection control unit. Future research on prevention of nosocomial infections by improving processes through health care worker performance is encouraged. Special attention should perhaps be given to understanding the determinants of behavior among "transient" health care providers and strategies that work to improve them.
Thesis (MS Clinical Epidemiology)--University of the Philippines Manila.
Keywords: Pneumonia -- Prevention; Artificial respiration